GSM based automatic greenhouse watering system / Ainur Afiqah Ahmad Azam and Nurul Munirah Zamberi - Ahmad Azam, Ainur Afiqah; Zamberi, Nurul Munirah (2015)
The system proposed in this project is 'Green House Watering System using GSM' which is a smart technology to provide plants and trees the required nourishment from the sunlight and to prevent the plant on the greenhouse from the harmful effects. System components used are humidity and temperature sensor, soil moisture sensor, transistor switches, relay nodes for automatic control, and arduino to control greenhouse information. The system is implemented using low power wireless components that are Arduino UNO. At the same time, we are using Proteus Software to stimulate the circuit to make this more efficient. A model of greenhouse is achieved. It was possible to do control plant growth through closely studying relationship between indoor environmental information and monitored information on crop itself. It is made possible to collect information and control effectively and automatically of greenhouse in the site or from a remote place through GSM modem.